Analysis of Chemistry Interest Level in Merdeka Curriculum Implementation at SMA Negeri 8 Pontianak - Rachma Julianty Putri; Hairida Hairida; Rahmat Rasmawan; Erlina Erlina; Maria Ulfah (Universitas Negeri Medan, 2024)
Elective subject is the flagship program of Merdeka Curriculum..The elective subject program is based on students’ interest, talents, and aspirations. Therefore, students’ interest level in chemistry, as one of the options for elective subject program is a necessary to determined. This study aims to determine the level of student interest in choosing chemistry as an elective subject, so that teachers could find the best alternatives to increase students’ interest. The research was conducted with quantitative analysis methods and descriptive statistical approaches, using 139 students of grade 11th who have chosen chemistry as the elective subject. The level of students’ interest in chemistry is measured by students’ interest questionnaire. The questionnaire was adopted and developed by aspects of students’ interest: teachers’ role, students’ perception, students’ intrinsic motivation in learning, and meaningful learning of lesson. Content validation test using Aiken formula showed the questionnaire validity is very high, as value 1. Based on the analysis, the result stated that the level of students’ interest was included as high category with 76,11%. All aspects are categorized as high, aspects of the teacher's role in learning with 77.44%, students’ perceptions with 73.63%, students’ intrinsic motivation 78.99% and the meaningfulness of learning lesson with 74.37%.